Association Between NR3C1 Mutations and Glucocorticoid Resistance in Children With Acute Lymphoblastic Leukemia - Liu, Haiyan; Li, Ziping; Qiu, Fei; Li, Chunjie; Lin, Xiaojing; He, Yingyi; Qian, Maoxiang; Song, Yuanbin; Zhang, Hui (Frontiers in Pharmacology, 2021)
Treatment outcomes in children with acute lymphoblastic leukemia (ALL) have been improved substantially, with a cure rate exceeding 80% using conventional therapy. However, the outcome for patients with relapsed/refractory ALL remains unsatisfactory, despite the fact that these patients generally receive more intense therapy. Glucocorticoid (GC) resistance is a leading cause of treatment failure and relapse in ALL. Abnormal NR3C1 transcription and/or translation is strongly associated with GC resistance, but the underlying molecular mechanism and the clinical value of NR3C1 alterations with GC resistance in ALL treatment remain unclear. This study applied panel sequencing to 333 newly diagnosed and 18 relapsed ALL samples to characterize the link between NR3C1 and ALL further. We identified NR3C1 mutations in three patients with newly diagnosed ALL (0.9%) and two patients with relapsed ALL (11.1%). Functional analyses revealed that four of these five NR3C1 mutations (p.R477H, p.Y478C, p.P530fs, and p.H726P) were loss-of-function (LoF) mutations. A drug sensitivity test further showed that LoF NR3C1 mutations influence GC resistance. Saturated mutagenesis of hotspot R477 demonstrated the importance of this residue for NR3C1 function. The dominant-negative effect of p.R477C and p.R477S and the non-dominant negative effect of p.R477H and p.Y478C suggests multiple mechanisms underlying GC resistance. Thus, primary or acquired genomic lesions in NR3C1 may play a critical role in GC resistance and contribute to ALL treatment failure and/or relapse.